2015
DOI: 10.1080/01490451.2014.901438
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria and Diatoms in Biofilms of Two Karstic Streams in Germany and Changes of Their Communities Along Calcite Saturation Gradients

Abstract: Biofilms microscopically dominated by cyanobacteria and diatoms of two CO 2 degassing karst-water creeks in Germany were investigated for their diversities along a gradient of calcification using SSU rRNA gene cloning and sequencing from environmental samples. The recovered totals of 731/413 cyanobacteria/diatom clones were grouped at 97/98% similarity levels into 28/29 molecular OTUs widely spread over their corresponding sequence phylogenies forming mostly monophyletic subclades. Sequence comparisons with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Our isolates 3 and 2a appear to belong to their OTU5, which is related to the type strain of Tychonema bourrellyi CCAP 1459/11 [59]. The phylogenetic tree of Brinkmann et al [36] did not include the clones identical to our dominant strain, and therefore, we can only guess that it belongs or is closely related to their clade B. This would also correspond to the Tychonema/ Phormidium/Microcoleus clade found with a metagenomic study by Schneider et al [60].…”
Section: The Travertine Deposition In Hoyoux River Systemmentioning
confidence: 90%
See 3 more Smart Citations
“…Our isolates 3 and 2a appear to belong to their OTU5, which is related to the type strain of Tychonema bourrellyi CCAP 1459/11 [59]. The phylogenetic tree of Brinkmann et al [36] did not include the clones identical to our dominant strain, and therefore, we can only guess that it belongs or is closely related to their clade B. This would also correspond to the Tychonema/ Phormidium/Microcoleus clade found with a metagenomic study by Schneider et al [60].…”
Section: The Travertine Deposition In Hoyoux River Systemmentioning
confidence: 90%
“…The Hoyoux sequences are in bold and the travertine and tufa sequences from elsewhere are printed in italics. The OTU numbers are taken from Brinkmann et al [36] and the 'Unid.' number from Arp et al [17] Phormidium tubules are broken and exposed to the environmental water so that the carbonate precipitation takes place inside the tubules as well (Fig.…”
Section: Relationship Between Cyanobacteria and Carbonate Depositsmentioning
confidence: 99%
See 2 more Smart Citations
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%